(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article discusses the role and effectiveness of modern teaching methods in delivering the “Natural Sciences” subject to primary school students. It highlights the importance of interdisciplinary integration, the STEAM approach, digital technologies, experiments, and practical activities. The paper also explores methods for developing students’ thinking skills, engaging them in active learning processes, and fostering a conscious attitude toward nature.